Board cultural diversity and firm performance under competitive pressures - Olga Dodd; Bart Frijns; Robin Kaiji Gong; Shushu Liao (Financial Review, 2023)
We examine the impact of board cultural diversity, based on directors' ancestry, on firm performance conditional on product market competition. We argue that culturally diverse boards foster critical thinking and offer creative solutions that help firms thrive in competitive environments. We document that culturally diverse boards are associated with superior performance for firms operating in highly competitive industries. To address potential endogeneity issues, we use a quasi-natural experiment of the U.S. import tariff cuts. The positive impact of board cultural diversity on firm performance in competitive markets manifests itself in firms that innovate more, require creative inputs, and face heightened predation risk due to their high interdependence with industry rivals, in line with culturally diverse boards effectively performing their advisory role. Lastly, we find no evidence that board cultural diversity is associated with enhanced monitoring as its benefits fade in the presence of powerful CEOs.
Keywords: 330; board diversity; board of directors; competition; cultural diversity; firm performance; product market